2015
DOI: 10.4338/aci-2014-09-ra-0084
|View full text |Cite
|
Sign up to set email alerts
|

Computer decision support changes physician practice but not knowledge regarding autism spectrum disorders

Abstract: SummaryObjective: To examine whether adding an autism module promoting adherence to clinical guidelines to an existing computer decision support system (CDSS) changed physician knowledge and self-reported clinical practice.Methods: The CHICA (Child Health Improvement through Computer Automation) system, a CDSS, was enhanced with a module to improve management of autism in 2 of the 4 community pediatric clinics using the system. We examined the knowledge and beliefs of pediatric users using cross-sectional surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…The weak point in the process appears to be the clinical response to screening results, as evidenced by the apparent nonresponse of physicians to almost half of positive M-CHAT results. 30 This finding is consistent with previous work on clinical decision support systems. 37,38 In fact, the greater than 50% response rate achieved by CHICA is high compared with other types of physician alerts, which may be ignored more than 90% of the time.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The weak point in the process appears to be the clinical response to screening results, as evidenced by the apparent nonresponse of physicians to almost half of positive M-CHAT results. 30 This finding is consistent with previous work on clinical decision support systems. 37,38 In fact, the greater than 50% response rate achieved by CHICA is high compared with other types of physician alerts, which may be ignored more than 90% of the time.…”
Section: Discussionsupporting
confidence: 91%
“…This method also has the advantage of ensuring that scoring is done correctly. The weak point in the process appears to be the clinical response to screening results, as evidenced by the apparent nonresponse of physicians to almost half of positive M-CHAT results . This finding is consistent with previous work on clinical decision support systems .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Three studies reported on the use of automated EHR [ 22 , 32 , 35 ] to facilitate screening procedures within pediatric clinics. Both Bauer et al [ 22 ] and Downs et al [ 32 ] (see also [ 59 ], not included in this review) implemented the Child Health Improvement Through Computer Automation system (CHICA). CHICA is a computer decision support system developed to facilitate surveillance and screening for ASD in primary pediatric care services by implementing automated administration and scoring of the M-CHAT.…”
Section: Resultsmentioning
confidence: 99%